The effect of single-bulb garlic oil extract toward the hematology and histopathology of the liver and kidney in mice - Sri Rahayu Lestari; Muhaimin Rifai (Universidade de São Paulo, 2019)
Single garlic has been used as a traditional medicine for hypercholesterolemia and increasing stamina. The aim of this research was to analyze the effect of single-bulb garlic oil (SGO) extract toward hematology and histopathology liver and kidney in mice. Male mice (strain Balb-C, 12 weeks old, weight of 28±3 g) was treated by SGO for 28 days (once per days) with various doses K- (Normal); K+ (SGO 0.0 mg/kg BW); T1 (SGO 6.25 mg/kg BW); T2 (SGO 12.5 mg/kg BW); T3 (SGO 25.0 mg/kg BW); T4 (SGO 50.0 mg/kg BW). The end of the treated mice was sacrificed. Blood was collected to analyze hematology. Liver and kidney were collected then made microanatomy slide with Hematoxylin-Eosin staining. Parameters of hematology are the levels of hemoglobin, hematocrit, number of erythrocytes, and number of leukocytes. Histopathology of liver and kidney determine by cell necrosis. The result of the research showed that SGO increased the number of erythrocytes and leucocytes but there is no effect on the levels of hemoglobin and hematocrit. Histopathology on liver and kidney showed there is no effect in necrosis. The conclusion is the single-bulb garlic oil extract safe if consumed continuously